Profile of neonatal epilepsies: Characteristics of a prospective US cohort - Shellhaas, Renée A. (Neurology, 2017)
OBJECTIVE: Although individual neonatal epilepsy syndromes are rare, as a group they represent a sizable subgroup of neonatal seizure etiologies. We evaluated the profile of neonatal epilepsies in a prospective cohort of newborns with seizures. METHODS: Consecutive newborns with seizures were enrolled in the Neonatal Seizure Registry (an association of 7 US children's hospitals). Treatment and diagnostic testing were at the clinicians' discretion. Neonates with seizures related to epileptic encephalopathies (without structural brain abnormalities), brain malformations, or benign familial epilepsies were included in this analysis. RESULTS: Among 611 consecutive newborns with seizures, 79 (13%) had epilepsy (35 epileptic encephalopathy, 32 congenital brain malformations, 11 benign familial neonatal epilepsy [BFNE], 1 benign neonatal seizures). Twenty-nine (83%) with epileptic encephalopathy had genetic testing and 24/29 (83%) had a genetic etiology. Pathogenic or likely pathogenic KCNQ2 variants (n = 10) were the most commonly identified etiology of epileptic encephalopathy. Among 23 neonates with brain malformations who had genetic testing, 7 had putative genetic etiologies. Six infants with BFNE had genetic testing; 3 had pathogenic KCNQ2 variants and 1 had a pathogenic KCNQ3 variant. Comorbid illnesses that predisposed to acute symptomatic seizures occurred in 3/35 neonates with epileptic encephalopathy vs 10/32 with brain malformations (p = 0.03). Death or discharge to hospice were more common among newborns with brain malformations (11/32) than those with epileptic encephalopathy (3/35, p = 0.01). CONCLUSIONS: Neonatal epilepsy is often due to identifiable genetic causes. Genetic testing is now warranted for newborns with epilepsy in order to guide management and inform discussions of prognosis.